Towards recognition of peer violence in youth sports – the case of Vojvodina - Ivana Milovanović; Radenko Matić; Jovan Vuković; Milica Blagojević; Mladen Mikić; Dragan Marinković (Exercise and Quality of Life)
The paper contains the results of the field research that the authors used in order to determine the existence and manifesting forms of peer pressure in youth sports. The sample consists of young people aged 11 to 18, who practice sport (N=536). The research was conducted in the second half of 2019 in the territory of the Autonomous Province of Vojvodina. The research results indicate that there are various forms of aggressive and violent behavior among youth, among which psychological violence predominates. The most common place for violence is the dressing room, after training or a competition. In terms of age, high-school-age children report higher level of violence victimization compared to older primary school children. The research results Introduction DOI: 10.31382/eqol.200603  The aggression and violence are global social phenomena, which have been researched in the past three decades. By examining many definitions of aggression it can be concluded that it is any “behavior that is intended to harm another person who is motivated to avoid that harm” (Allen & Anderson, 2017: 2; Bushman & Huesmann, 2010; DeWall, Anderson, & Bushman, 2011); whereas violence is, among other things, described as an “extreme form of aggression that has severe physical harm (e.g.,serious injury or death) as its goal” (Allen & Anderson, 2017: 3; Anderson & Bushman, 2002; Bushman & Huesmann, 2010; Huesmann & Taylor, 2006). testify to the fact that sport shares “the fate” of the society in which it exists and that policy makers in youth sports should take into consideration this social phenomenon as well.